1979
DOI: 10.1111/j.1365-2222.1979.tb01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgE antibodies to platinum salts in sensitized workers

Abstract: Summary A RAST has been developed for the measurement of IgE antibodies specific to platinum chloride complexes in sensitized workers. Human serum albumin covalently linked to Sepharose beads by the cyanogen bromide method was reacted with ammonium tetrachloroplatinite (II) (NH4)2PtCl4. This conjugate was more suitable for the RAST, than conjugates of HSA and the platinum salt prepared in solution and then linked to the activated Sepharose, showing better sensitivity and giving lower levels of non‐specific upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(48 citation statements)
references
References 10 publications
(1 reference statement)
0
47
1
Order By: Relevance
“…More than 50% of exposed persons may develop symptoms and signs of immediatetype allergy such as conjunctivitis, rhinitis, asthma bronchiale or urticaria [2][3][4], Characterization and clinical rel evance of other cutaneous complaints including pruritus and dermatitis are uncertain [2,3,8]. The diagnosis of Pt-related occupational disease can be confirmed by skin prick test or bronchoprovocation eliciting immedi ate-type reactions to minute doses (10~2 to 10"8 mol/l) of [Pt(IV)Cl6]2-or [Pt(II)Cl4]2- [5,7,9], In contrast to the highly specific but hazardous in vivo tests, attempts to elu cidate the nature of these reactions by demonstrating Ptspecific serum IgE or IgG antibodies in vitro remained in conclusive [7,10], even though elevated total IgE levels were found in Pt-exposed refinery workers [5][6][7], Further more, it has been shown that Pt salts are able to elicit non specific histamine release from human basophils in vitro [71.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of exposed persons may develop symptoms and signs of immediatetype allergy such as conjunctivitis, rhinitis, asthma bronchiale or urticaria [2][3][4], Characterization and clinical rel evance of other cutaneous complaints including pruritus and dermatitis are uncertain [2,3,8]. The diagnosis of Pt-related occupational disease can be confirmed by skin prick test or bronchoprovocation eliciting immedi ate-type reactions to minute doses (10~2 to 10"8 mol/l) of [Pt(IV)Cl6]2-or [Pt(II)Cl4]2- [5,7,9], In contrast to the highly specific but hazardous in vivo tests, attempts to elu cidate the nature of these reactions by demonstrating Ptspecific serum IgE or IgG antibodies in vitro remained in conclusive [7,10], even though elevated total IgE levels were found in Pt-exposed refinery workers [5][6][7], Further more, it has been shown that Pt salts are able to elicit non specific histamine release from human basophils in vitro [71.…”
Section: Introductionmentioning
confidence: 99%
“…Hexachloroplatinate-mediated histamine release from washed leucocytes of sensitized workers is significantly greater than from the leucocytes of nonexposed subjects (13,18). Use of the radioallergosorbent test (RAST) has revealed specific IgE antibodies to the complex chloroplatinate3 (3,14,18). The allergenic potency of the platinum salts is determined by their electric charge and the number of reactive halide ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The disease meets the following criteria for an allergic etiology: (i) asymptomatic interval (5, 11), (ii) only a portion of the exposed subjects reacting (5), (iii) reaction to exposure to minimal air concentrations (4, 15), (iv) symptoms more likely to appear in atopic individuals (5,11,16), (v) hyposensitization successful (9), and (vi) specific antibodies of the IgE type demonstrated (3,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…There are a few exceptions in which the presence of specific serum IgE and/or a positive SPT are considered a sensitive diagnostic aid, e.g. to complex (unconjugate) platinum salts, trimellitic and acid anhydrides [18,19]. In the case of LMW compounds, particularly some of the most common causes of OA, like isocyanates, the sensitivity and specificity of tests assessing the IgE response is variable, being good for some [20] and less satisfactory for others [21,22].…”
Section: Immunological Assessmentmentioning
confidence: 99%